Youth Suicide As Tillichian Anxiety And Courage: An Existential Reading Of Two Popular American Young Adult Novels - Tan, Sin Tien (2018)
Current conceptualization of youth suicide can be argued to be limited and incomplete for it alienates the suicidal person. Suicide is seen to be caused by overbearing societal or psychological pressure and it is consequently portrayed in a passive and defeatist light. This study aims to explore the process of humanization of the suicidal person by offering an alternative conceptualization of youth suicide. This is done through the usage of fiction as a lens to understand real life suicide. It studies the suicides that are portrayed in Jay Asher’s Thirteen Reasons Why and Julie Ann Peters’ By the Time you Read This, I’ll be Dead. The study adopts a framework from the school of existentialism as the philosophy has a unique focus on the individual experience of human as a free self-deterministic agent against a seemingly meaningless universe. It could humanize the concept of suicide by providing understanding from the subjective perspective of the suicidal person. Specifically, the study employs Tillichian existentialism because Tillich’s systematic ways of philosophizing can provide a structured and comprehensive model to help understand the suicide phenomenon. Objectives of the study include interpreting Tillichian anxiety as suicide causes and the characters’ suicide as Tillichian courage in the two selected novels. It investigates how anxiety figures into the characters’ decision to commit suicide and how their suicides overcome said anxiety, thus constituting them as forms of Tillichian courage. This alternative reading of youth suicide in the two novels offers an invaluable glimpse into the suicidal person’s psyche.